Dr 16S rRNA Sequence Indicates Presence of Unculturable Bacteria in Postpartum Uterus of Buffalo - Dar, Shabaz Hussain; Qureshi, Salauddin; Sankar, Muthu; Mehrotra, Sanjeev; Patra, Manas K; Singh, Sanjay K; Kumar, Harendra; Krishnaswamy, Narayanan (The Indian Journal of Animal Reproduction, 2023)
Bacterial contamination of the uterus is inevitable during the first three weeks of calving in the cow. The potential importance of unculturable bacteria in the establishment of postpartum endometritis is reported in the cow; however, existence of unculturable bacteria is not known in the postpartum uterus of the buffalo. Accordingly, sterile endometrial swab was collected in peptone water on day 20-21 post-calving from Murrah buffalo (n=12) without vaginal contamination and bacterial gDNA was isolated. Using gene specific primers, 16S rRNA was amplified by PCR. The purified PCR product was sequenced and was compared in Ribosomal database project (RDBP). Genetic distance was calculated using multiple alignments with ClustalW model in MegAlign module of Lasergene Package. The phylogenetic relationship was analyzed using the software MEGA 5.1 by neighbourhood joining method. The results revealed that invariably every sample contained uncharacterized bacteria (100%); however, no new species of was found. The clinical significance of uncharacterized bacteria in the establishment of postpartum endometritis needs to be determined in the buffalo.